Confined and propagating optical phonons in double-channel AlGaN/GaN heterostructures. (October 2021) - Zhou, X.J.; Lei, D.; Men, K.N.M.L.; Xing, Y.
Abstract: Based on the dielectric continuous model, the confined and propagating optical phonon modes in AlGaN/GaN double-channel heterostructures are studied by using the transfer matrix method. Their dispersion relations and electrostatic potentials are discussed considering the ternary mixed crystal and size effects. The results show that both confined and propagating phonon modes can be classified into two groups: low- and high-frequency modes. Ternary mixed crystal effect only affects the low-frequency confined phonons, but has little influence on the high-frequency ones. The thicknesses of the AlGaN barriers have a significant impact on the confined phonons oscillating in both barriers and channels, but the thicknesses of the GaN channels only affect the confined phonons oscillating in channels. It is also found that the propagating modes can be ignored in the further researches because of the narrow frequency range allowing them to exist. These findings indicate that the scattering from the optical phonons in double-channel heterostructures can be modulated to improve the performance of related devices by adjusting the Al composition of AlGaN and the size of each layer. Highlights: Confined and propagating optical phonon modes were studied in AlGaN/GaN double-channel heterostructures. The dispersion relation and electrostatic potential of phonon were analyzed in this structure. The ternary mixed crystal effect and size effect were discussed in detail. The anisotropy of wurtzite nitrides was included.